2009
DOI: 10.1021/ci900040z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Intrinsic Hydrogen Bond Acceptor Strength of Organic Compounds by Local Molecular Parameters

Abstract: A quantum chemical model has been developed for predicting the hydrogen bond (HB) acceptor strength of monofunctional organic compounds from electronic ground-state properties of the single molecules. Local molecular parameters are used to quantify electrostatic, polarizability, and charge transfer components to hydrogen bonding, employing the ab initio and density functional theory levels HF/6-31G** and B3LYP/6-31G**. The model can handle lone pairs of intermediate and strong HB acceptor heteroatoms (N, O, S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 30 publications
(49 reference statements)
3
48
0
2
Order By: Relevance
“…QM methods are more accurate than MM based alternatives due to the fact they consider the underlying physics of a given molecular system more precisely [15,[30][31][32][33][34][35]. However, they are rarely used for this purpose due to their perceived high computational demand and the relatively few cases studies reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…QM methods are more accurate than MM based alternatives due to the fact they consider the underlying physics of a given molecular system more precisely [15,[30][31][32][33][34][35]. However, they are rarely used for this purpose due to their perceived high computational demand and the relatively few cases studies reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This relatively simple approximation has led to the development of in-silico tools using small probe molecules to estimate H-bond strength which can prove very useful in lead optimization efforts [30][31][32][33][34][35]. However, simplifications involved in these models might mask SAR in cases where the generic probes are not fully representative of the receptor, or the effect of the local active site conformation is important.…”
Section: Qm Analysis Of Fragment-like Kinase Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…6. 43 Therefore it should interact more strongly with the framework m-(OH) groups along the backbone of MIL-53(Fe), explaining why it displaces isopropanol more easily. In doing this we have assumed that the decreasing peak area of the starting phase is inversely related to the growth of the fully open phase, i.e., we assume that the initial phase is replaced directly by the open phase, as indicated by the contour graphs.…”
Section: In Situ Edxrdmentioning
confidence: 99%
“…These descriptors were originally introduced by Klamt 32,33 and were successfully applied to the estimation of the hydrogen bonding strength, 34,35 a process observed between the hydroxyl groups of HO-PBDEs and the amino acid residues of TRβ, acting as a characteristic interaction for the thyroid hormone activity of HO-PBDE molecules. 20,30 In addition, these parameters have also been shown capable of addressing the electrostatic interactions, 34,35 another important molecular interaction that governs the activity of HO-PBDEs to TRβ. 20,30 Consequently, the local molecular descriptors are expected to be capable of quantifying the electronic interactions between HO-PBDEs and TRβ and to explain the activity mechanism because of their explicit physicochemical meanings.…”
Section: ■ Introductionmentioning
confidence: 99%